A fast white balance algorithm based on pixel greyness. Issue 3 (March 2017) - Thai, Ba; Deng, Guang; Ross, Robert
Abstract The goal of automatic white balance (AWB) is to maintain colour constancy of an image by removing colour cast caused by un-canonical illuminant. In this paper, we address two limitations associated with a class of AWB algorithms and propose a technique to estimate the illuminant which takes into consideration the internal illumination and all pixels of the image. The estimate is calculated by a weighted average of all pixels. The weight for a pixel is determined from the greyness. The greyness of a pixel is measured from its chroma Cb and Cr in the YCbCr colour space. The experimental results demonstrate that performance of the proposed technique is competitive with that of state-of-the-art AWB algorithms. The proposed algorithm can be implemented in real-time applications, such as in consumer digital cameras due to its low computational complexity.